Measure Effectiveness of Reproductive Health Education Programs Teenagers in Schools Intermediate: Evaluation Results in the Cileunyi Region Bandung Regency - Nadeak, Bernadetha; Prihantini; Atep Jejen; Astuti, Hutari Puji; Aden Sutiapermana; Handayani (PT Inovasi Pratama Internasional, 2023)
This article discusses the results of evaluating the effectiveness of the Adolescent Reproductive Health Education Program in secondary schools in the Cileunyi area, Bandung Regency. The approach used in this research is a combination of participatory, field research and active monitoring. The main objective of this research is to measure the level of success and impact of the program in increasing knowledge, attitudes and reproductive health behavior of adolescents. This study combines a participatory approach, field research, and active monitoring to gain a comprehensive picture of the program's effectiveness. A participatory approach involves collaboration with program participants, teachers, and local stakeholders to design and implement activities. Field research was carried out by conducting surveys, interviews and direct observations at selected secondary schools in the Cileunyi area. Active monitoring involves continuous data collection throughout the study period. Findings The evaluation results showed a significant increase in students' knowledge regarding reproductive health, with a high level of participation in discussion activities, workshops and outreach sessions. Positive attitudes and behavioral changes were also observed after participating in the program. Collaboration with local stakeholders and active student participation are considered key factors for success. Therefore, a combination of participatory approaches, field research and active monitoring has proven effective in measuring and evaluating the Adolescent Reproductive Health Education Program in the Cileunyi area. These findings provide valuable insights for program administrators, schools, and other stakeholders to improve the design and implementation of similar programs in the future.